Early supplemental α2‐macroglobulin attenuates cartilage and bone damage by inhibiting inflammation in collagen II‐induced arthritis model. (4th January 2019) - Li, Shengchun; Xiang, Chuan; Wei, Xiaochun; Sun, Xiaojuan; Li, Ruifang; Li, Pengcui; Sun, Jian; Wei, Dinglu; Chen, Yong; Zhang, Yanxiang; Wei, Lei
Abstract: Objective: To determine if early supplemental intra‐articular α2‐macroglobulin (A2M) has a chondroprotective effect in a collagen II‐induced arthritis (CIA) mice model. Methods: DBA/1 mice were randomized into four groups (n = 15/group): (a) CIA + 1.2 μg of A2M; (b) CIA + 0.8 μg of A2M; (c) CIA + 0.4 μg of A2M; (d) vehicle + phosphate‐buffered saline (PBS). A2M was injected into right ankles and PBS was injected into the left ankles simultaneously as internal control at days 36, 43 and 50. The CIA inflammation clinical score and ankle thickness were recorded every other day starting on day 21 until sacrifice. Changes in inflammation were monitored by in vivo fluorescence molecular tomography (FMT). Inflammation, cartilage and bone damage were assessed with X‐ray, histology and immunohistochemistry. Cartilage and inflammation‐related gene expression was quantified by real‐time polymerase chain reaction (PCR). Results: All mice showed ankle inflammation on day 33. After day 43, lower clinical scores, ankle thickness and Sharp/van der Heijde method scores in A2M‐treated ankles compared with PBS‐treated ankles. FMT data indicated that the inflammation markers MMPSense and ProSense were significantly elevated in the PBS‐treated ankles than A2M‐treated ankles. Histology and X‐ray analyses indicated that A2M administration resulted in lower levels of inflammatory infiltration and synovial hyperplasia, as well as more typical cartilage and bone organization with increased COL II and Aggrecan staining when compared with PBS‐treated ankles. In addition, real‐time PCR showed that, matrix metalloproteinase‐3, ‐9, ‐13, COL X and Runx2 were significantly less expressed in A2M‐treated groups than PBS‐treated animals. Conclusion: Early supplemental intra‐articular A2M exerts an anti‐inflammatory effect and attenuates cartilage and bone damage in a CIA model.